2022
DOI: 10.31234/osf.io/dfqeg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-Term Consequences of Repeated School Closures During the COVID-19 Pandemic for Reading and Mathematics Competencies

Abstract: School closures during the first wave of the COVID-19 pandemic in early 2020 were associated with attenuated learning gains compared to pre-pandemic years. In Germany, two further pandemic waves led to school closures and periods of remote learning between December 2020 and May 2021. The present study investigates the academic achievement of all incoming fifth-graders in the federal state of Baden-Württemberg before and during the pandemic, using educational large-scale assessment results in reading and mathem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Our study considered different sources of statistical uncertainty, plausible value variance, sampling variance, and imputation variance, as well as weighting, which imposed a high standard on finding significant changes in achievement gaps. There are recent findings from the German federal state Baden-Württemberg based on an annual population survey suggesting that schools with a large proportion of students with migration background and with lower average socio-cultural capital, respectively, had larger average losses in achievement than other schools ( Schult et al, 2022 ). Therefore, it is likely that studies using larger samples or longitudinal designs can identify significant differences in achievement gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Our study considered different sources of statistical uncertainty, plausible value variance, sampling variance, and imputation variance, as well as weighting, which imposed a high standard on finding significant changes in achievement gaps. There are recent findings from the German federal state Baden-Württemberg based on an annual population survey suggesting that schools with a large proportion of students with migration background and with lower average socio-cultural capital, respectively, had larger average losses in achievement than other schools ( Schult et al, 2022 ). Therefore, it is likely that studies using larger samples or longitudinal designs can identify significant differences in achievement gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Tezer, Cavus Orkun, Osum and Türe (2021), in their study examining primary school students' views on mathematics lessons during the COVID-19 pandemic process, stated that fifth grade primary school students in Northern Cyprus have difficulty in understanding online lessons and need help while doing their homework. Schult, Mahler, Fauth, and Lindner (2022) state that the mathematics courses conducted during the pandemic process, cause mathematics learning losses in the 5th grade students who have a low socio-cultural level in Germany. Apart from these, a study conducted in Jordan by Abuhammad (2020) addresses the personal, logistical, and technical barriers associated with the distance learning during the COVID-19 quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…There have been plenty of research investigating the learning loss during or just after the school closures due to the pandemic. Almost all of them found significant learning losses [24,25,27,[31][32][33][34][35][36]38,39]. Early meta-reviews showed that virtually all studies found learning losses in different contexts [22,[41][42][43]56].…”
Section: Plos Onementioning
confidence: 99%
“…In one of these, Kaffenberger [28] argued that three months of school closure may result in a learning loss that amounts to more than one year of learning gains, but she also claimed that most of these losses can be recovered through remediation programmes after returning to school. Some researchers used educational data sources on skills and learning that were collected before and after the pandemic [24,25,[30][31][32][33][34][35]. For example, Engzell and others [25] used a national exam data in the Netherlands, which was conducted just before and after an eight-week-school lockdown.…”
Section: Introductionmentioning
confidence: 99%